Factors Affecting the Efficiency of Digital-Era Work Performance among Accountants in Pathum Thani Province - ใจภิภักดิ์ ณัฐพงษ์; พาหา ปนัดดา; เครือหงษ์ พีระพร; เรืองหร่าย รัชภูมิ; อิศรางกูร ณ อยุธยา กิตติวัฒน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: 1) examine the level of digital-era work performance efficiency among bookkeepers; 2) compare the efficiency of digital-era work performance among bookkeepers classified by personal factors; and 3) investigate work-related factors influencing digital-era work performance efficiency among bookkeepers. The sample consisted of 365 bookkeepers in Pathum Thani Province. The statistical techniques employed for data analysis included percentage, mean, standard deviation, t-test, F-test, and multiple regression analysis (MRA). The results of the study revealed that: 1) the overall level and individual dimensions of digital-era work performance efficiency among bookkeepers in Pathum Thani Province were at a moderate level. Among the dimensions, reduction of errors in recording and data processing was ranked at the highest level, followed by work speed, accuracy of accounting information and reports, and quality of accounting outputs, respectively. 2) Bookkeepers with different genders demonstrated statistically significant differences in overall work performance efficiency, as well as in reduction of errors in recording and data processing, at the .05 level of statistical significance. Furthermore, bookkeepers with different ages and work experiences showed statistically significant differences in performance efficiency in terms of the quality of accounting outputs at the .05 level. 3) Digital-era work-related factors were found to significantly influence overall digital-era work performance efficiency at the .01 level of statistical significance. The factors, ranked from highest to lowest influence, were accounting information system capability (β = .345), digital technological knowledge and understanding (β = .267), continuous professional development (β = .209), and management support (β = .126), respectively.